(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2023)
Emotional intelligence is one of the new concepts in psychology, which is constantly being studied by many scientists. The article analyses the concepts of emotional intelligence, emotional competence and its structural components. The article considers various concepts of emotional intelligence of such scientists as P. Salovey, D. Mayer, D. Caruso, G. Gardner, R. Bar-On, S. Marcus, G. Dudchak, M. Mykolaychak. The article also analyses domestic concepts of emotional intelligence. As a result of the analysis of various scientific views on the concept of emotional intelligence and methods of its research, it has been made a decision to develop the author’s own psychodiagnostic test. The author has developed own test methodology for studying the emotional component, since there are no similar test methods in the national psychodiagnostics. The author’s methodology includes five main and two additional scales. The main scales of the methodology include the following properties of emotional intelligence: 1. managing one’s own emotions; 2. managing the emotions of others; 3. understanding one’s own emotions; 4. understanding the emotions of others; 5. empathy. Additional scales of the methodology are the lying scale and the general level of emotional intelligence (calculated by adding the results of the 5 main scales). Subsequently, various test methods were considered to study emotional intelligence and its components. The following tests were chosen for correlation: Toronto Alexithymia Scale, N. Hall’s Self-Esteem Emotional Intelligence Inventory, and the Profile of Emotional Competence (PEC). A correlation analysis of the own methodology with existing test methods for the study of emotional intelligence has been carried out to confirm its validity. The study proved the validity and reliability of the developed test methodology. Therefore, the developed test methodology is indeed aimed at studying the general level of emotional intelligence and studying its components such as: managing one’s own emotions and the emotions of others, understanding one’s own emotions and the emotions of others, empathy.